Return on investment : strategies for profit - Rachlin, Robert (London. : Prentice-Hall. International, Inc., 1976)
This book analysed return on investment concepts and applications. Ìt's assumed that a business has a prime objective of generating an adequate return to the owner's.
Include index
ucj 14/01/2019
Loans
Keywords: Investments; Rate of return